Pengaruh penambahan tepung biji durian sebagai bahan penstabil terhadap kualitas es krim susu kambing etawa [Effect of durian seed flour addition as a stabilizer on the quality of Etawa goat’s milk ice cream] - Susilawati Susilawati; Samsul Rizal; Murhadi Murhadi; Muhammad Nur Faza Taqiyyuddin (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Utilization of durian seed flour (DSF) in the manufacture of Etawa goat milk ice cream has the potential to be developed. This study aimed to study the effect of DSF as a stabilizer on the quality of Etawa goat milk ice cream. The study used a completely randomized block design with a single factor in the form of five DSF concentration levels, namely 0, 1.5, 3, 4.5, and 6% with 5 replications and 0.5% gelatin as a control. Parameters of ice cream quality analyzed include physical characteristics such as overrun, melting speed, and emulsion stability and sensory characteristics such as color, texture and overall acceptability. The variance tests were carried out on the research data, followed by the Honest Significant Difference (BNJ) test at the 5% level. The results showed that DSF concentration significantly affected the physical properties of overrun, melting speed, and emulsion stability and affected the sensory characteristics of color, texture, and overall acceptability of Etawa goat's milk ice cream. TDSF concentration of 3% produces goat's milk ice cream with the best characteristics which has an overrun value of 33.40%, melting speed of 25 minutes, 83% emulsion stability with a soft texture, yellowish white color, and protein, fat and total solids content according to SNI no. 01-3713-2018.